EMPLOYEE ENGAGEMENT IN HUMAN RESOURCE PRACTICE - Mochamad Rizki Sadikin (Universitas Brawijaya, 2021)
This article explains employee engagement in form of human resource. It explains from what is engagement, the theory related to engagement, some research in employee engagement and how employee engagement. Conclusion in the article is when engagement locked in worker, it would give the company points of competitive advantages—including higher efficiency, customer satisfaction and lower representative turnover. The relationship between worker engagement and organizational results would be greater in the event that superior measures were utilized.